Immature Platelet Fraction in Thrombocytopenic Patients (TALENTA Publisher, Universitas Sumatera Utara, 2021)
Bone marrow puncture (BMP), is usually performed to identify thrombopoiesis activity and is still the gold standard to determine the etiology of thrombocytopenia. This diagnostic test is invasive hence it may cause discomfort to the patient. One of noninvasive test to determine the etiology of thrombocytopenia is by measuring immature platelet fraction (IPF). IPF is highly correlated to the activity of thrombopoiesis and by understanding the value, clinicians are able to use it in determining whether or not invasive examination is needed and more importantly avoiding unnecessary platelet transfusion. This research was a cross-sectional descriptive observational study aimed to evaluate IPF value in thrombocytopenic inpatients in the Department of Internal Medicine, Haji Adam Malik Hospital Medan. 83 people were recruited, 48 were female (57.83%) and 35 were male (42.16%). IPF values ranged 0,5-59,6% using Sysmex XN-1000 (reference range 1-4,8%). There were 5 (6.02%) low IPF values, 29 (34.93%) normal IPF values and 49 (59.03%) high IPF values. Evaluation of IPF in thrombocytopenic patients is a promising tool to discriminate central from peripheral thrombocytopenia.